Feasibility of an endoscope-dominated side-to-end hypoglossal-facial anastomosis: an anatomical study - Yang, Xiaobing; Man, Dulegeqi; Yang, Yang; Li, Xingang (Frontiers in Surgery, 2023)
Objective A surgical simulation of an endoscope-dominated side-to-end hypoglossal-facial anastomosis was performed to evaluate the feasibility. Methods Eight anatomical cadaver heads (16 sides) were recruited. The steps in conventional procedures were abbreviated or omitted. A facial nerve was first harvested near its external genu and was used for a side-to-end hypoglossal-facial anastomosis. The stump of the used facial nerve was truncated and recycled immediately caudal to the facial recess in another anastomosis and then recycled again at the stylomastoid foramen. As a recycled stump becomes too short to ensure a side-to-end anastomosis, the hypoglossal nerve was transected in situ, and an endoscopic end-to-end hypoglossal-facial anastomosis was attempted. Surgical simulation and quantitative measurement methods were used to analyze the anastomosis effects of different harvested sites of the facial nerve. Results Several steps in the conventional procedures provide little benefit in endoscopic surgery. A facial nerve stump recycled at the stylomastoid foramen is too short to ensure a tensionless side-to-end anastomosis. An endoscopic end-to-end hypoglossal-facial anastomosis was feasible, although it required more time than the classical microsurgical anastomosis. The greater agility of an endoscope enables the conventional surgical steps to be overlapped or interweaved into the procedure. Conclusions The multiple surgical fields and ability to manipulate the viewpoint provided by an endoscope have brought about breakthroughs in classical surgical paradigms. In addition, it is best to choose the sites of the facial nerve harvested near the external genu. If unavailable, an alternative section site could be selected immediately caudal to the facial recess, but cannot be distal to the stylomastoid foramen. The length of the stump should be individualized and preferably optimized with a nerve stimulator.